2020
DOI: 10.1126/sciadv.abc8696
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and regulatory maps of decidua-derived stromal cells inform gene discovery in preterm birth

Abstract: While a genetic component of preterm birth (PTB) has long been recognized and recently mapped by genome-wide association studies (GWASs), the molecular determinants underlying PTB remain elusive. This stems in part from an incomplete availability of functional genomic annotations in human cell types relevant to pregnancy and PTB. We generated transcriptome (RNA-seq), epigenome (ChIP-seq of H3K27ac, H3K4me1, and H3K4me3 histone modifications), open chromatin (ATAC-seq), and chromatin interaction (promoter captu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 91 publications
0
51
0
Order By: Relevance
“…HAND2 expression was almost entirely restricted to cell populations in the endometrial stromal fibroblast lineage (see Materials and methods for cell type naming convention), with particularly high expression in ESF2s and DSCs ( Figure 2A ). Interestingly, while it is generally thought that ESFs are not present in the pregnant endometrium, previous studies have demonstrated that ESFs retain a presence in the endometrium from the first trimester all the way to term ( Richards et al, 1995 ; Suryawanshi et al, 2018 ; Muñoz-Fernández et al, 2019 ; Sakabe et al, 2020 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…HAND2 expression was almost entirely restricted to cell populations in the endometrial stromal fibroblast lineage (see Materials and methods for cell type naming convention), with particularly high expression in ESF2s and DSCs ( Figure 2A ). Interestingly, while it is generally thought that ESFs are not present in the pregnant endometrium, previous studies have demonstrated that ESFs retain a presence in the endometrium from the first trimester all the way to term ( Richards et al, 1995 ; Suryawanshi et al, 2018 ; Muñoz-Fernández et al, 2019 ; Sakabe et al, 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, it is bound by transcription factors that establish endometrial stromal cell type identity and mediate decidualization, including the progesterone receptor (PGR), NR2F2 (COUP-TFII), GATA2, FOSL2, FOXO1, as well as polymerase II ( Figure 2C ). The HAND2 promoter loops to several distal enhancers, as assessed by H3K27ac HiChIP data generated from a normal hTERT-immortalized endometrial cell line (E6E7hTERT), including a region bound by PGR, NR2F2, GATA2, FOSL2, and FOXO1, that also contains SNPs associated with gestation length in recent GWAS ( Warrington et al, 2019 ; Sakabe et al, 2020 ; Figure 2C ). HAND2 was significantly upregulated by decidualization of human ESFs into DSCs by cAMP/progesterone treatment (Log 2 FC = 1.28, p = 2.62×10 −26 , FDR = 1.16×10 −24 ), and significantly downregulated by siRNAs targeting PGR (Log 2 FC = −0.90, p = 7.05×10 −15 , FDR = 2.03×10 −13 ) and GATA2 (Log 2 FC = −2.73, p = 0.01, FDR = 0.19) ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of transcriptomic, chromatin accessibility ( Buenrostro et al, 2015 ) and chromatin conformation capture ( Kempfer and Pombo, 2020 ) data in the integrative analyses are expected to inform about the functional impact of chromatin modification changes. These approaches are technically complex and computationally demanding, but also extremely informative, as has been demonstrated recently with decidual cells ( Sakabe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear accumulation of the H3K27me3 demethylase, lysine demethylase 6A (KDM6A), has been detected concomitantly with this process, which suggests that epigenetic mechanisms, including the removal of the suppressive H3K27me3 mark, take part in the transition ( Nancy et al, 2018 ). Very recently, a comprehensive analysis of chromatin landscape changes has been reported in endometrial fibroblasts decidualized in vitro ( Sakabe et al, 2020 ). Chromatin accessibility using the ATAC-seq technique, ChIP-seq with H3K4me1, H3K27ac, and H3K4me3 antibodies, and promoter capture Hy-C to detect distant regulatory elements, were integrated and matched with RNA-seq data in this large-scale genome-wide study.…”
Section: Deciduamentioning
confidence: 99%